COOPERATIVE GAMES IN THE ACTIONS OF THE A UNIÃO FAZ A VIDA PROGRAM IN THE NORTH OF RIO GRANDE DO SUL, BRAZIL (Fiep Bulletin - online, 2013)
The present paper is the result of a Master's research on Education; it aims to investigate the impact that Cooperative Games, through the actions of the A União Faz a Vida (Union Makes Life) Program, have had on the knowledge and teaching practices of public school teachers in the north of the state of Rio Grande do Sul, Brazil, from the perspective of the teaching collective. The study was conducted in four municipalities that implemented the program until 2004. The following presuppositions gave rise to the research: a) We live in times and with social agendas that have potentiated individual isolation and that made the schools vulnerable, schools seen herein as spaces of significant learning experiences; b) “cooperative games” express an experience in the “pedagogy of cooperation”; c) teachers signify their practices based on their own experience; d) motivation and challenges coming from spaces located outside the walls of the official teaching system may modify teaching knowledge. The guidelines established by the Law on Education Guidelines and Basis (LDB), No. 9.394/96, and the principles of “Cooperative Games” served as reference to the analysis of the educative practices and processes in this study. The knowledge problem of the study was: What impact are cooperative games by means of the A União Faz a Vida Program making on the knowledge and the pedagogical practices of teachers who work in public schools in the region, from the perspective of this teaching collective? The study design used a qualitative and descriptive approach. Participating individuals were two teachers per school participating in the Program; teachers were chosen according to a criterion of representativeness. Study tools were document analysis, a questionnaire, and an interview. The analytical process showed that the guidelines of the A União Faz a Vida Program conceived by Sicredi produced new forms of relationship in the sphere of the school communities studied. These new forms of relationship have particularly improved cooperative dynamics in the pedagogical practice in all courses.
Keywords: Cooperative games; teaching knowledge; pedagogical practices